Valuing individual animals through tourism: Science or speculation? - Catlin, James; Hughes, Michael Phillip; Jones, Tod; Jones, Roy; Campbell, R. (Elsevier, 2013)
Non-consumptive wildlife tourism plays an important role both in raising conservation issues and in providing economic support for conservation initiatives. Although the direct value of wildlife has been historically associated with its consumption, tourism is increasingly being used to value wildlife for its economic and environmental qualities. There are various methods by which these values can be assessed. In particular, there is a recent trend towards ascribing tourism values to individual animals. Such approaches enable direct comparisons with the extractive of use animals. These calculations can depict clear contrasts in value in tourism’s favour which can then be publicised to a wider audience. Whilst this method may appear desirable, this paper demonstrates that valuations made at the scale of single animal are frequently based on assumptions that may not withstand critique. In turn it is argued, that given the flaws in this method, instead of enhancing arguments for conservation it has the potential to weaken its case. It is contended that using tourism to value wildlife should be conducted at a destination or higher level where the arguments have a firmer scientific basis and thus more impact and relevance.